High Prevalence of Transmitted Drug Resistance in Acute HIV-Infected Thai Men Who Have Sex With Men. (1st April 2015) - Ananworanich, Jintanat; Sirivichayakul, Sunee; Pinyakorn, Suteeraporn; Crowell, Trevor A.; Trichavaroj, Rapee; Weerayingyong, Jessica; Chomchey, Nitiya; Fletcher, James L. K.; van Griensven, Frits; Phanuphak, Praphan; Robb, Merlin L.; Michael, Nelson L.; et al.
Abstract : Abstract: As use of antiretroviral therapy in Thailand increases, so does the potential for transmission of drug-resistant HIV. We describe the prevalence of WHO surveillance drug resistance mutations among 120 subjects who underwent genotypic testing during acute HIV infection in Bangkok, Thailand. In this cohort of predominantly men who have sex with men, we observed an overall transmitted drug resistance prevalence of 9.2%, including nucleoside/nucleotide analog reverse transcriptase inhibitor 5.0%, nonnucleoside analog reverse transcriptase inhibitor 3.4%, and protease inhibitor 3.4%. These prevalence estimates are higher than previous reports of transmitted drug resistance in Thailand. Baseline drug resistance testing may be warranted, particularly among men who have sex with men.